Towards a European Full Employment Policy - Jo Ritzen; Klaus F. Zimmermann (Global Labor Organization (GLO), 2018)
Full employment in the European Union member states is a challenge but feasible, also in downswings of the business cycle and during stages of increased robotization. It requires a labor legislation that ensures flexibility and retraining, responsive labor sharing during the business cycle and to individual life cycle needs, government interventions to supply supplemental employment and revamping dual education. The future of work is better ensured with coordinated European full employment labor policies establishing fair work conditions based on long-run business strategies as well as a fair distribution of national income between labor and capital.
Keywords: J5; J8; 330; Employment; full employment; future of work; robotization; fair work; work-sharing; employment regulations; basic income; vocational training